Epidemiology and prevention of rugby injuries amongst schoolboy, senior club and provincial rugby players in the Western Cape - Upton, Patrick Anthony Howard (MRC/UCT RU for Exercise and Sport Medicine, 2018)
This thesis comprises a series of independent investigations examining rugby injuries occurring to players from under 14 to senior provincial level in the Cape Province (now the Western Cape). The first two studies report data aimed at gaining a more detailed understanding of rugby injuries in specific populations or under specific conditions, whilst the remainder of the thesis reports injury data from both a retrospective and a prospective epidemiological survey involving the same 3990 boys from 25 high schools. Following publication of data showing a progressive rise in the number of spinal cord injuries in the Western Cape, coupled with a sustained media attack on the attitudes of the (then) South African Rugby Board, certain experimental law changes were introduced to South African schoolboy rugby in 1990 and 1991. The purpose of the law changes was either to make the game safer or to make it more open and flowing, or both. Accordingly, the studies described in chapters 4 -8 set out to analyse the effects of these law changes on the incidence and nature of rugby injuries. This was accomplished by comparing data with a similar study conducted in 1983 and 1984 in the same 25 schools (Roux, 1992). The study reported in chapter 2 determined whether the use of neoprene (thermal) pants might reduce the risk of hamstring injury amongst 60 senior club rugby players, all of whom had previously sustained a hamstring muscle tear. The rationale was that the few seasons prior to this 1992 study had been characterised by an increasing use by rugby players of thermal or neoprene pants; a practice which seemed to have evolved spontaneously and without any scientific assessment of its value. We concluded that the wearing of thermal pants can reduce the risk of hamstring injury during rugby. However, other risk factors for injury are probably more important. These include levels of preseason physical fitness, correct warm up and stretching procedures before activity and adequate rehabilitation before returning to activity following injury. The objective of the study reported in chapter 3 was to determine the influence of preseason strength and endurance training on risk of injury in rugby players from two South African provincial teams during the 1992 rugby season. Players from one province followed a supervised scientifically-designed physical training programme, while those from the other did not follow a structured programme. The findings of the study, the first study to prove the relationship between pre-season preparation and early season injury, showed that inadequate pre-season endurance training is a major contributor to the high injury rate at the beginning of the season amongst provincial rugby players. Further, strength and endurance training are interrelated as risk factors. Thus, compared to players with adequate strength and endurance training, those with adequate strength training and insufficient endurance training are at greatest risk of injury, followed by players with insufficient strength and endurance training. It was also shown that contact practices 2 days after inter-provincial match contributed more to an increased number of injuries than to success; that "niggling" injuries may develop into more serious injury if players attempt to "play through" them; and that the lack of structured treatment and rehabilitation of an injury places players at risk of being re-injured.